2015
DOI: 10.3390/rs71215818
|View full text |Cite
|
Sign up to set email alerts
|

Maize Leaf Area Index Retrieval from Synthetic Quad Pol SAR Time Series Using the Water Cloud Model

Abstract: Abstract:In order to monitor crop growth along the season with synthetic aperture radar (SAR) images, radiative transfer models were developed to retrieve key biophysical parameters, such as the Leaf Area Index (LAI). The semi-empirical water cloud model (WCM) can be used to estimate LAI values from SAR data and surface soil moisture information. Nevertheless, instability problems can occur during the model calibration, which subsequently reduce its transferability in both time and space. To avoid these ill-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…Summer crops also achieved good classification results. Corn, with an F1-score of~75%, was characterized by a rather insensitive VV curve, and on the contrary, a clear increase in VH due to volume scattering during the vegetative growth phase (250-300 days) until the plants reached their maximum height [46], after which it remained rather constant. Rice achieved an F1-score of~85%, mainly due to its characteristic time signature due to flooding at the time of sowing, which led to very low backscatter due to specular reflection [47].…”
Section: Crop Classification Results With Regard To Its Temporal Signmentioning
confidence: 97%
“…Summer crops also achieved good classification results. Corn, with an F1-score of~75%, was characterized by a rather insensitive VV curve, and on the contrary, a clear increase in VH due to volume scattering during the vegetative growth phase (250-300 days) until the plants reached their maximum height [46], after which it remained rather constant. Rice achieved an F1-score of~85%, mainly due to its characteristic time signature due to flooding at the time of sowing, which led to very low backscatter due to specular reflection [47].…”
Section: Crop Classification Results With Regard To Its Temporal Signmentioning
confidence: 97%
“…This confirms that biweekly composites cannot adequately characterise crop productivity if crop critical periods are smoothed by the compositing algorithm 8 and implies that the use of maximum LAI or Early/Late Windows LAI was driven by practicality and data availability rather than by systematic targetting of critically sensitive periods suggested by crop physiology. Integrating radar data 40,41 and blending lower resolution time series 42,43 are two mitigation options to increase data frequency in areas with persistent cloud cover. Attention should be paid to correct the spatial scaling bias when fusing LAI data 44,45 because it does not correlate linearly with spatial resolution 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…A new LAI estimation approach was developed though the coupling of two existing models, the WCM and the Ulaby soil moisture model. Beriaux et al (2015) used the water cloud model and a Bayesian fusion method to estimate maize LAI, and the result showed that this method has great potential in improving the accuracy and reliability of LAI retrieval using C-band SAR data. Crop biomass estimation Plant biomass plays an important role in ecosystem mechanisms.…”
Section: Crop Height Estimationmentioning
confidence: 99%